Covid In Parenteral Viral Hepatitis 19 Forgiveness of Infection (Eurasian Medical Research Periodical, 2022)
This article provides information on the course, clinical manifestations, treatment stages and immunity of Covid 19 infection in patients with parenteral viral hepatitis.